Improving Fiqh Learning Outcomes Through the Use of Audio-Visual Media for the Topic of Obligatory Bath (Case Study at MIN 2 Seluma) - Elmi Susi; Dedy Novriadi; Syukri Amin; Lety Febriana; Desi Firmasari (CV. Edujavare Publishing, 2026)
This study aims to analyze the use of audiovisual media in improving student learning outcomes regarding the topic of mandi wajib (obligatory ritual bathing) in the fourth-grade Fiqh (Islamic jurisprudence) subject at Madrasah Ibtidaiyah Negeri 2 Seluma. The study was motivated by the fact that classroom instruction was still dominated by one-way lecturing methods, and some students did not yet fully grasp the correct procedure for mandi wajib as prescribed by the Prophet Muhammad (PBUH). A case study method with a qualitative approach was employed, involving the Fiqh teacher and fourth-grade students as research subjects. Data were collected through participant observation, in-depth interviews, and documentation. The results indicate that the use of audiovisual media had a positive impact on improving the *Fiqh* learning outcomes of fourth-grade students at MIN 2 Seluma regarding the *mandi wajib* topic. A significant improvement was observed after the audiovisual media was implemented in a structured manner over several sessions; the number of students achieving the Minimum Mastery Criteria (KKM) rose to 16 (100% mastery). The use of audiovisual media significantly enhanced the quality of learning across cognitive (material comprehension), affective (attitude toward the lesson), and psychomotor (practical worship skills) domains. Students became more active and enthusiastic, and found it easier to understand procedural material. Furthermore, this media strengthened the teacher's role as a facilitator and created a more interactive and contextual learning atmosphere. In conclusion, the use of audiovisual media had a tangible impact on improving student learning outcomes across cognitive, affective, and psychomotor aspects. This reinforces the idea that appropriate media does not merely enhance the delivery of instruction but also fosters the achievement of educational goals in a comprehensive manner.